THE RELATIONSHIP OF MONEY ETHICS ON TAX EVASION WITH INTRINSIC RELIGIOSITY, EXTRINSIC RELIGIOSITY, AND MATERIALISM AS MODERATING VARIABLES (CASE ON PRIVATE TAXPAYERS LISTED IN KPP PRATAMA TERNATE) - Ansar, Resmiyati; Mahdi, Suriana A. R; Susi, Wa (ACCOUNTABILITY, 2018)
This study aims to find out the influence of money ethics on tax evasion with intrinsic religiosity, extrinsic religiosity, and materialism as moderating variables. The sample is selected by using convinience sampling method with sample size of a 100 respondents as primary data. This study uses simple regression and moderated regression analysis for hypothesis testing. The result of this study shows that money ethics has an effect on tax evasion, intrinsic religiosity moderarates the relationship between money ethics and tax evasion. Extrinsic religiosity does not moderate the relationship bertween money ethics and tax evasion. Materialism moderates the relationship between money ethics and tax evasion.